La apologética teológica en tiempos de pandemia (2021)
The central thesis of this reflection study considers the times of the coronavirus as a relevant historical event for the exercise of a new theological apologetics. The thesis presupposes an apologetic exercise capable of helping to integrate the gift of God's love in these times of crisis for the whole human family and is based on the Petrine programmatic exhortation to be "always ready to give an account of our hope to anyone who asks us. But to do so with humility and respect" (1P 3,15-16). The study concludes by emphasizing the vehemence of the good news of the Lord's resurrection as an event capable of igniting the heart of suffering humanity with a flame of hope.